A Riffaterrean Semiotic Reading of Nizar Qabbani’s Poem ‘Uhibbuki Jiddan’ - Ayu Siwi Wening Nurahnis; Haris Shofiyudin; Mahfuzd Muhammad Shodiq (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2025)
Purpose— This study aims to analyze the poem “Uhibbuki Jiddan” by Nizar Qabbani using Michael Riffaterre’s semiotic theory. It explores how signs, models, variants, matrices, and hypograms contribute to constructing meaning in the text. Design/methods/approach— Employing a qualitative descriptive method, the analysis applies Riffaterre’s two-level reading approach—heuristic (denotative) and hermeneutic (interpretative)—followed by identification of the model, variant, matrix, and hypogram elements found in the poem. Findings— The study reveals that the poem reflects the model of “impossible love”, expanded into three variants: love, uncertainty, and sacrifice. The matrix expresses the idea that love cannot be predicted by logic, but is sensed through emotional and bodily experiences. The hypogram links the poem to another of Qabbani’s poems, “Inni Uhibbuki”, reinforcing the central theme of sincere, unrequited affection. Research Implications— This research contributes to Arabic literary criticism by demonstrating how Riffaterre’s semiotics can uncover hidden emotional structures in romantic poetry. It also highlights the depth of Qabbani’s poetic expression and his ability to transform personal emotion into universal poetic symbols.